Jawabanmu

2014-08-16T05:44:59+07:00
1. (x+5) (x-3) = x² - 3x + 5x -15
                    = x²+2x-15

2. (x+6) (x-2) = x²-2x+6x-12
                    = x²+4x-12

3. (x-5) (x+5) = x²+5x-5x-25
                   =x²-25

4. (x-7) (x-3) = x²-3x-7x+21
                  =x²-10x+21

5. (y+11)(y+12) = y²+12y+11y+132
                      = y²+23y+132

semoga membantu
1. (x+5) (x-3) = x² - 3x + 5x -15
= x²+2x-15

2. (x+6) (x-2) = x²-2x+6x-12
= x²+4x-12

3. (x-5) (x+5) = x²+5x-5x-25
=x²-25

4. (x-7) (x-3) = x²-3x-7x+21
=x²-10x+21

5. (y+11)(y+12) = y²+12y+11y+132
= y²+23y+132
2014-08-16T05:46:09+07:00
1.(x+5) (x-3)=?
⇔ x²-3x+5x-15=0
⇔  x²+2x+15=0

2.(x+6) (x-2)=?
⇔ x²-2x+6x-12=0
⇔ x²+4x-12=0

3,(x-5) (x+5)
⇔ x²+5x-5x-25=0
⇔ x²-25=0

4. (x-7) (x-3)=?
⇔ x²-3x-7x+21=0
⇔ x²-10x+21=0

5.(y+11) (y+2)=?
⇔ y²+2y+11y+22=0
⇔ y²+13y+22=0

semoga membantu :)